Indonesia’s Forest Resource Monitoring - Belinda Arunarwati Margono; Ahmad Basyirudin Usman; Budiharto .; Ruandha Agung Sugardiman (Indonesian Journal of Geography, 2016)
Forest cover in term of distribution, extent and types, is major information required to manage the forest resources. Notably for Indonesia, which covers by approximately 98 Mha (>50%) forests, consist of 93 Mha (49.6%) natural forest and 5 Mha (2.6%) plantations forest. The forests are invaluable, including significantly preserve carbon, maintain unique biodiversity, support water and mineral cycle, as well as support local and global community. Here we report efforts have been made for years in the Ministry of Forestry for providing land cover information. Those efforts are including early development, data sources selection, method employed, techniques, and classification scheme, as well as problem encountered and approach for improvements.